100 Opportunities for More Inclusive Ocean Research: Cross-Disciplinary Research Questions for Sustainable Ocean Governance and Management - Wisz, Mary S.; Satterthwaite, Erin V.; Fudge, Maree; Fischer, Mibu; Polejack, Andrei; St. John, Michael; Fletcher, Stephen; Rudd, Murray A. (Frontiers in Marine Science, 2020)
In order to inform decision making and policy, research to address sustainability challenges requires cross-disciplinary approaches that are co-created with a wide and inclusive diversity of disciplines and stakeholders. As the UN Decade of Ocean Science for Sustainable Development approaches, it is therefore timely to take stock of the global range of cross-disciplinary questions to inform the development of policies to restore and sustain ocean health. We synthesised questions from major science and policy horizon scanning exercises, identifying 89 questions with relevance for ocean policy and governance. We then scanned the broad ocean science literature to examine issues potentially missed in the horizon scans and supplemented the horizon scan outcome with 11 additional questions. This resulted in an unprioritized list of 100 general “how can we (a given society) respond to...” questions that would require a cross-disciplinary approach to inform policy. The questions fell into broad categories including: coastal and marine environmental change, managing ocean activities, governance for sustainable oceans, ocean value, and technological and socio-economic innovation. Each question can be customized by ecosystem, region, scale, and socio-political context, and is intended to inspire discussions of salient cross-disciplinary research directions to direct scientific research that will inform policies. Governance and management responses to these questions will best be informed by drawing upon a diversity of natural and social sciences, local and traditional knowledge, and engagement of different sectors and stakeholders.